The Response of Muslim Viewers to the Images of the end of day in 2012: a case studi of student of English Departement of Sunan Kalijaga State Islamic University of Yogyakarta - Rakhma Tri Pratiwi (Fak. Adab dan Ilmu budaya UIN Sunan Kalijaga, 2013)
Hard1/oen, 01